An extended view on inequality and redistribution in the European Union - The role of indirect taxation and in-kind benefits - Michael Christl; Silvia De Poli; Monika Köppl-Turyna (Global Labor Organization (GLO), 2024)
This paper refines the concept of disposable income by incorporating governmentprovided in-kind benefits for education and health services, as well as imputed VAT payments, following Figari and Paulus (2015). Our analysis reveals that including these elements significantly reduces income inequality, as seen in a decrease in the Gini coefficient across all examined countries. While direct taxes and cash benefits are the main drivers of redistribution, in-kind benefits also play a substantial role, while VAT having a smaller, negative impact. Our study highlights that additionally extending the income concept increases also the targeting of the tax benefit system to low-income households, however to a very different extend across the EU Member States. Our new, broader approach allows for more accurate assessments of redistribution and cross-country comparisons, offering valuable insights for EU-level policy evaluations.
Keywords: H23; I38; H24; D31; 330; tax-benefits model; EUROMOD; welfare state; in-kind benefits; indirect taxes; redistribution